Integrating mental health into primary care : a global perspective (World Health Organization, 2008)
This report on integrating mental health into primary care, which was developed jointly by the World Health Organization (WHO) and the World Organization of Family Doctors (Wonca), presents the justification and advantages of providing mental health services in primary care. At the same time, it provides advice on how to implement and scale-up primary care for mental health, and describes how a range of health systems have successfully undertaken this transformation.Mental disorders affect hundreds of millions of people and, if left untreated, create an enormous toll of suffering, disability and economic loss. Yet despite the potential to successfully treat mental disorders, only a small minority of those in need receive even the most basic treatment. Integrating mental health services into primary care is the most viable way of closing the treatment gap and ensuring that people get the mental health care they need. Primary care for mental health is affordable, and investments can bring important benefits. This report is divided into distinct parts, with different needs in mind. Part 1 provides the context for understanding primary care for mental health within the broader health care system. Part 2 explains how to successfully integrate mental health into primary care and highlights 10 common principles which are central to this effort. It also presents 12 detailed case examples to illustrate how a range of health systems have undertaken this transformation. Finally, Annex 1 provides information about the skills and competencies that are required to effectively assess, diagnose, treat, support and refer people with mental disorders. As this report shows that treating mental disorders as early as possible, holistically and close to the person\'s home and community lead to the best health outcomes. In addition, primary care offers unparalled opportunities for the prevention of mental disorders and mental health promotion, for family and community education, and for collaboration with other sectors.
Keywords: Primary Health Care; Mental Health Services; Mental Disorders; veřejné zdravotnictví; psychiatrie; zdravotně postižení; služby péče o duševní zdraví; duševní poruchy; primární zdravotní péče